2015
DOI: 10.1371/journal.pone.0143973
|View full text |Cite
|
Sign up to set email alerts
|

Money Affects Theory of Mind Differently by Gender

Abstract: Theory of Mind (ToM) ─ the ability to understand other’s thoughts, intentions, and emotions ─ is important for navigating interpersonal relationships, avoiding conflict, and empathizing. Prior research has identified many factors that affect one’s ToM ability, but little work has examined how different kinds of monetary incentives affect ToM ability. We ask: Does money affect ToM ability? If so, how does the effect depend on the structure of monetary incentives? How do the differences depend on gender? We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 77 publications
0
19
0
2
Order By: Relevance
“…Ma-Kellams and Blascovich (2013) also revealed that money increases independent self-construal, F(1, 119) = 9.79, p = .002, d = 0.37, and dampens collective self-construal, F(1, 119) = 5.33, p = .023, d = 0.25, supporting the aforementioned shift from communalism to individualism. Similarly, participants' accuracy in inferring others' mental states was found to vary with the form and structure of incentives (Ridinger & McBride, 2015). Specifically, female participants performed significantly worse when they were told that they would be paid $0.40 for each correct answer than when no incentive was mentioned, β = −1.42, p = .03, 95% confidence interval [CI] [−2.72, −0.12], suggesting that money dampened intrinsic motivation to display empathy.…”
Section: Stream 2: Money and Reduced Other-oriented Behaviormentioning
confidence: 97%
“…Ma-Kellams and Blascovich (2013) also revealed that money increases independent self-construal, F(1, 119) = 9.79, p = .002, d = 0.37, and dampens collective self-construal, F(1, 119) = 5.33, p = .023, d = 0.25, supporting the aforementioned shift from communalism to individualism. Similarly, participants' accuracy in inferring others' mental states was found to vary with the form and structure of incentives (Ridinger & McBride, 2015). Specifically, female participants performed significantly worse when they were told that they would be paid $0.40 for each correct answer than when no incentive was mentioned, β = −1.42, p = .03, 95% confidence interval [CI] [−2.72, −0.12], suggesting that money dampened intrinsic motivation to display empathy.…”
Section: Stream 2: Money and Reduced Other-oriented Behaviormentioning
confidence: 97%
“…Further research showed that money-related incentives or thoughts reduce the accuracy of emotional inferences (Ma-Kellams, & Blascovich, 2013), compassion towards unfortunate others (Molinsky, Grant, & Margolis, 2012;Stellar, Manzo, Kraus, & Keltner, 2012), and perspective-taking (Sheldon & Kasser, 1995;Van Laer, De Ruyter, & Cox, 2013). They also undermine motives to perceive a mind in irrelevant targets (Wang & Krumhuber, 2017) and impair theory of mind ability (Ridinger & McBride, 2015).…”
Section: The Moderating Role Of Moneymentioning
confidence: 99%
“…The ability of understand what others will do in game theoretic situations depends crucially on the ability to recognize the others utility function and their beliefs. This ability is known as ToM and typically after the age of five children are often described as having ToM [25,26]. ToM is often described as a discrete phenomenon where a person either possesses it or has a deficit.…”
Section: Prior Literaturementioning
confidence: 99%
“…ToM is often described as a discrete phenomenon where a person either possesses it or has a deficit. However, research has shown even in non-clinical adult populations there can be substantial variation in ToM ability [25][26][27]. One issue in prior research on individual differences in ToM is that measures of ToM often exhibit ceiling effects making it difficult to observe any heterogeneity in ToM ability [27].…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation